Accounting values and inflation - Baxter, William T.; Institute of Chartered Accountants in England and Wales, London (London ; New York : McGraw-Hill, 1975)
This book amplifies the case against historical accounts, and discusses the pros and cons of reform. It sets out the various proposals for improvement - asset revaluation, measurement of loss on holding money, adjustment of input costs with indices, and so on.
"Sponsored by the Research Committee of the Institute of Chartered Accountants in England and Wales."
Includes index.
Includes bibliographical references: p. 192-194.
osa 29/01/2019
Loans
Keywords: Accounting